Understanding AI’s role in reshaping labour markets - Temirbayeva, D.M.; Akylbayeva, D.B. (Академик Е.А.Бөкетов атындағы Қарағанды университетінің баспасы, 2024)
The rapid advancement of Artificial Intelligence (AI) impacts significant transformations across societies, economies, and the world of work. While AI holds immense potential to enhance productivity through task automation, personalization, and quality control, it also raises critical questions about its impact on labor markets. This paper explores the nuanced effects of AI on employment, emphasizing its dual potential to disrupt and augment human labor. Drawing on task-based frameworks and microdata, the study identifies varied outcomes across occupations, highlighting that task automation does not necessarily imply job losses but may complement human roles, fostering efficiency and productivity. However, the integration of AI technologies into workplaces raises concerns about job quality, worker autonomy, and employment stability, particularly in sectors driven by algorithmic management. Policymakers must address these challenges by fostering skill development, supporting workforce transitions, and ensuring equitable access to AI-driven opportunities. The study underscores the importance of ongoing research to assess AI's dynamic interplay with labor markets and its broader socioeconomic implications, enabling a balanced and inclusive transition to an AI-integrated economy.
Keywords: Artificial Intelligence (AI); employment; occupations; workplace; labour; automation; job complementarity; integration